Compensation of hole conductivity in CdTe crystals doped with Cr - Nikonyuk, E.S.; Zakharuk, Z.I.; Kuchma, M.I.; Kovalets, M.O.; Rarenko, A.I.; Yuriychuk, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We present the results of optical and electrophysical investigations of CdTe:Cr crystals. A model explaining a considerable shift of the fundamental absorbtion edge in the crystals into the long-wave region is proposed. It is found that the doping of cadmium telluride crystals with Cr impurity leads to the introduction of deep donors with Еv + 0.19…0.32 eV